Italian Libyan Relations 1951 – 1969 Eecnomic Study - Rahman, Zeina Raad Abdel; Rahman, Muhammad Imad Redeef Abdel (South Eastern European Journal of Public Health, 2024)
This study explores the economic dimensions of Italian-Libyan relations from 1951 to 1969, a period marked by the shifting sands of post-colonial geopolitics and economic development. After Libya's independence in 1951, Italy, as a former colonial power, sought to maintain and reshape its economic ties with the newly sovereign nation. This period witnessed significant Italian investment in Libyan infrastructure, oil exploration, and trade, reflecting both countries' evolving economic priorities and strategies. The study examines key agreements, economic aid, and the impact of the oil boom on bilateral relations. By analyzing trade data, investment flows, and political agreements, the research highlights how economic considerations influenced diplomatic interactions and contributed to the broader geopolitical landscape of the region. The findings provide insights into the complexities of post-colonial economic relationships and the strategic maneuvers of a former colonial power seeking to secure its interests in a rapidly changing world.